Formation of virtual community groups to manage prosumers in smart grids - Rathnayaka, A.J. Dinusha; Potdar, Vidyasagar; Dillon, T.; Kuruppu, S. (Inderscience, 2015)
In the context of energy generation and distribution networks, the emergence of smart grids has enabled bidirectional energy as well as information flow between energy users and utility grids, transforming traditional energy consumers into economically motivated prosumers, who not just consume energy but also generate green energy, and share the surplus with the main utility grid. Several studies have been carried out to manage the prosumers, and the concept of Prosumer–Community Groups (PCG) has provided a promising approach to achieve that end. However, this concept is still in its infancy and the related aspects have not been comprehensively studied so far. Therefore, in this research paper, we address the formation of PCG. The proposed framework classifies the prosumers' energy–sharing behaviours, while detecting the outliers, and characterises PCG. Further, we also demonstrate the practical functionality of the proposed framework using a prosumer data set.